Characterization of novel diorganotin(IV) complexes with O,N,O donor ligand. Derived from carbohydrazide: X-ray crystal structure of [Ph 2Sn(H2CBS)] - Affan, M. A.; Liew, Y. Z.; Ahmad, Fasihuddin; Shamsuddin, Mustaffa; Yamin, Bohari Mohamad (The Council of Scientific & Industrial Research, New Delhi, 2007)
A new series of diorganotin(IV) complexes has been synthesized by the reaction of R2SnCl2 (R = Me, Bu and Ph) with O,N,O-tridentate carbohydrazone ligand derived from carbohydrazide. Three diorganotin(IV) complexes of carbohydrazone-bis(salicylaldehyde) ligand [H 4CBS, (1)] with R2SnCl2 have been synthesized by refluxing in the presence of base in 1:2:1 molar ratio (metal:base:ligand). All the complexes (2-4) have been characterized by different physicochemical techniques like molar conductivity measurements, elemental analyses, UV-visible, IR and 1H NMR spectral studies. All complexes (2-4) are non electrolytic in nature. Among them, diphenyltin(IV) complex (4) has also been characterized by X-ray crystallography diffraction analyses. In the solid state, the carbohydrazone ligand (1) exists as the keto tautomer. But in solution in the presence of base and organotin(IV) chloride(s), it is converted to the enol tautomer and is coordinated to the tin atom in its deprotonated enolate form. X-ray crystallographic analysis shows that the diphenyltin(IV) complex, [Ph 2Sn(H2CBS)] (4), is five-coordinate and has a distorted trigonal-bipyramidal geometry with the ligand coordinated to the tin(IV) as a tridentate dinegative fashion through its phenolic-O, enolic-O and imine-N atoms. The general bond length order is: oxo < phenolato < enolato. The Sn-O (enolato) bond is longer than Sn-O (phenolato) bond by -0.095 Å and is identical with Sn-O (carboxylate) bond. The crystal of [Ph 2Sn(H2CBS)] (4) is triclinic with space group P-I with a = 8.514(2)Å, b = 12.505(3)Å, c = 12.794(4)Å, α = 105.169(4)°, β= 107.639(4)°, γ = 96.232(4)°, V = 1226.5(6) Å3, Z = 1 and Dcalc = 1.541 mg/m 3. The IR, UV and 1H NMR data are consistent with all the diorganotin(IV) derivatives having similar geometry.